Analisis Strategi Pengembangan Komoditas Unggulan Di Kabupaten Kutai Kartanegara - Dwijatenaya, Ida Bagus; Dewi, Mutiara Kartika (Jurnal Magrobis, 2015)
This study aims to determine strategies that will be used to develop competitive commodities. Research conducted in the Kutai regency in East Kalimantan province of Indonesia .The analytical tool used is the SWOT analysis .Some of the findings in this study are : ( a) in the district of Kota Bangun the development strategy of paddy rice field that is using a strategy of diversification , further strategy of development of fishery commodities cage by using a defensive strategy , and (b ) in the District Tenggarong Seberang development strategy paddy rice is an aggressive strategy as well as commodity development strategies cattle is using an aggressive strategy .Keywords: Strategy, commodities, featured